Parameters Associated with Adverse Fetal Outcomes in Parvovirus B19 Congenital Infection - Isabela Karine Rodrigues Agra; Antonio Gomes Amorim Filho; Lawrence Hsu Lin; Sckarlet Ernandes Biancolin; Rossana Pulcineli Vieira Francisco; Maria de Lourdes Brizot (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2017)
Abstract Objective To investigate the clinical and sonographic parameters associated with adverse fetal outcomes in patients with congenital parvovirus B19 infection managed by intrauterine transfusion. Methods This was a single-center retrospective study conducted from January 2005 to December 2016 that assessed patients with singleton pregnancies with fetal parvovirus infection confirmed by a polymerase chain reaction of the amniotic fluid or fetal blood samples who underwent at least one intrauterine transfusion. The maternal characteristics, sonographic findings and parameters related to intrauterine transfusion were compared between the two groups (recovery/non-recovery), who were categorized based on fetal response after in-utero transfusions. Progression to fetal death or delivery without fetal recovery after the transfusions was considered nonrecovery and categorized as an adverse outcome. Results The final analysis included ten singleton pregnancies: seven of which were categorized into the recovery group and three of which into the non-recovery group. The baseline characteristics were similar between the groups. All fetuses were hydropic at the time of diagnosis. No significant differences related to sonographic or intrauterine transfusion parameters were identified between the groups; however, the nonrecovery group tended to have an increased number of sonographic markers and lower fetal hemoglobin and platelet levels before the transfusion. Conclusion We were unable to firmly establish the clinical or sonographic parameters associated with adverse fetal outcomes in patients with parvovirus infection managed with intrauterine transfusions; however, edema, placental thickening and oligohydramnios may indicate greater fetal compromise and, subsequently, adverse outcomes. However, further studies are necessary, mainly due to the small number of cases analyzed in the present study.